2020
DOI: 10.1002/ps.5926
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of bioactive compounds and their association with different cowpea cultivars against their major stored pest

Abstract: Background: Stored grain insects are controlled with fumigant insecticides which can select resistant insect populations and cause environmental and applicator contamination. Thus, resistant cultivars and chemical constituents of essential oils are an alternative to the almost exclusive use of these insecticides. The effects of the combination of cowpea cultivars Vigna unguiculata (L.) Walp. with chemical constituents of essential oils against Callosobruchus maculatus were determined. Four cowpea cultivars: BR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Moussa Kéïta et al [25] with a drop in the emergence of C. maculatus adults to 0 and 4% follow exposure to EOs of Ocimum basilicum and Ocimum gratissimum. It was also reported that the emergence of C. maculatus F 1 adults was significantly inhibited by EO of Alpinia calcarata at concentrations of 0.80 g/L using fumigant toxicity [28]. Similarly, the emergence of C. maculatus has been previously reported to be also controlled by Allium sativum [21].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Moussa Kéïta et al [25] with a drop in the emergence of C. maculatus adults to 0 and 4% follow exposure to EOs of Ocimum basilicum and Ocimum gratissimum. It was also reported that the emergence of C. maculatus F 1 adults was significantly inhibited by EO of Alpinia calcarata at concentrations of 0.80 g/L using fumigant toxicity [28]. Similarly, the emergence of C. maculatus has been previously reported to be also controlled by Allium sativum [21].…”
Section: Discussionmentioning
confidence: 84%
“…Eugenol and (−)-menthone powerfully inhibited adult emergence C. maculatus adults [38]. e MOA by which terpenes can exert this insecticidal effect have been reported in an earlier work [28]. EO constituents can operate synergistically or individually depending on which insect pest is being targeted.…”
Section: Discussionmentioning
confidence: 87%
“…Bean resistance (Moraes et al 2011, Guzzo et al 2015, 2018, Eduardo et al 2016) and botanical insecticides , 2007, Barbosa et al 2002 have been largely studied for individual use against Z. subfasciatus in Brazil, with the identification of several genotypes resistant to the pest. The combination of plant resistance with botanical insecticides has been studied to control seed beetles (Coleoptera, Chrysomelidae, Bruchinae) in bean species worldwide (Lale and Mustapha 2000, Law-Ogbomo 2007, Tabadkani et al 2017, Barbosa et al 2020, with promising results from the economic and environmental perspectives, but little has been researched in relation to Z. subfasciatus (Luz et al 2017).…”
Section: Crop Production and Management Articlementioning
confidence: 99%
“…The natural environment likely holds a diversity of novel bioactive compounds, including those with the potential to be integrated with or replace synthetic compounds in the management of agricultural pests 3,16–19 . Plant‐based pesticides are currently among the most ecofriendly ways to control undesirable insects 20–25 . The plant species belonging to the Moracea family, especially those belonging to the genus Ficus , have been considered as promising sources for plant‐based bioactive compounds due to the presence of phenolic compounds, flavonoids, phytosterols, triterpenoids, volatile compounds, and coumarins 26–28 .…”
Section: Introductionmentioning
confidence: 99%